PENGARUH DISIPLIN KERJA, KOMPENSASI, DAN PANDEMI COVID 19 TERHADAP PRODUKTIVITAS PT. INDAH ROTI BERSERI PALEMBANG - Endang Kartikawaty; Tien Yustini; Fakhry Zamzam (Program Magister Manajemen Indo Global Mandiri University, 2021)
. The purpose of this study was to determine the Effect of Work Discipline, Compensation and the Covid-19 Pandemic Climate on the Productivity of PT. Indah Roti Berseri, Palembang partially or simultaneously. This research method uses descriptive and verification surveys, field data collection uses questionnaires, interviews and documentation techniques. This research is an associative research, where in this study there are variables that are related and can influence other variables. The population of this study were 77 employees of PT. Indah Roti Berseri, Palembang. Data processing using SPSS 25 analysis tool. Testing the data using the t test, that work discipline has an effect on productivity with t count 11.967 > t table 1.9912 and a significance of 0.00 <0.05, there is a compensation effect on productivity with t count 6.941 > t table 1.9912 and a significance of 0 ,00 < 0.05 , the COVID-19 pandemic climate affects performance with t count 11.489 > t table 1.9912 significance 0.00> 0.05 and work discipline, compensation and organizational climate during the pandemic on productivity simultaneously with f count 70.424 > f table 2.72 significance 0.00> 0.05. The common thread of research is that work discipline, compensation and the climate of the COVID-19 pandemic affect the productivity of PT. Indah Roti Berseri, Palembang both partially and simultaneously. A strategy to increase productivity by continuing to build the company's organizational climate even during the Covid 19 Pandemic and maintaining work discipline and employee welfare through good compensation.